The beneficial role of exercise in preventing doxorubicin-induced cardiotoxicity - Gaytan, Samantha L.; Lawan, Ahmed; Chang, Jongwha; Nurunnabi, Md; Bajpeyi, Sudip; Boyle, Jason B.; Han, Sung Min; Min, Kisuk (Frontiers in Physiology, 2023)
Doxorubicin is a highly effective chemotherapeutic agent widely used to treat a variety of cancers. However, the clinical application of doxorubicin is limited due to its adverse effects on several tissues. One of the most serious side effects of doxorubicin is cardiotoxicity, which results in life-threatening heart damage, leading to reduced cancer treatment success and survival rate. Doxorubicin-induced cardiotoxicity results from cellular toxicity, including increased oxidative stress, apoptosis, and activated proteolytic systems. Exercise training has emerged as a non-pharmacological intervention to prevent cardiotoxicity during and after chemotherapy. Exercise training stimulates numerous physiological adaptations in the heart that promote cardioprotective effects against doxorubicin-induced cardiotoxicity. Understanding the mechanisms responsible for exercise-induced cardioprotection is important to develop therapeutic approaches for cancer patients and survivors. In this report, we review the cardiotoxic effects of doxorubicin and discuss the current understanding of exercise-induced cardioprotection in hearts from doxorubicin-treated animals.